Correlation between Soil Transmitted Helminth Infection with Nutritional Status in Elementary School at Deli Serdang Regency North Sumatera - Andini, Leni; Nurfadly, Nurfadly (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: The prevalence of Soil Transmitted Helminth (STH) infections in Indonesia is still high, especially in elementary school children in North Sumatra Province. STH infection is thought to cause harm to nutrient requirements due to lack of calories, causing health and nutritional conditions to decline. Purposes: To determine the relationship of STH infection with nutritional status in 105926 State Elementary School students. Method: Analytic observational with cross sectional design. Sampling uses a total sampling method, with a total sample of 87 people. Nutritional status was determined by the CDC-NCHS 2000 growth curve and the determination of the STH infection used the Kato-Katz examination method. Results: 26 samples (29,9%) were positive and 61 samples (70,1%) were negative for STH infections. Positive samples infected with STH have nutritional status that is dominated by moderate and good nutritional status. Conclusion: There is no correlation between STH infection and nutritional status in 105296 State Elementary School students in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra.